Burden and its Determinants among Caregivers of Patients undergoing Hemodialysis - K.C, Nyamika; Chaudhary, Asmita; Dhami, Kabita; Bishwas, Anjali; K.C, Mamta; Bhattarai, Smita (Journal of Nobel Medical College, 2025)
Background: Chronic kidney disease affects more than ten percent of general population worldwide. Patients with end-stage renal disease require lifelong renal replacement which affects patient’s functioning leading to disruption of conventional lives of both patients and caregivers.The objective of this study was to identify the level of caregiver burden and to identify its determinants.Materials and Methods: A cross-sectional study was conducted in the dialysis unit of Nobel Medical College Teaching Hospital, Biratnagar from November 2024 to January 2025 following ethical approval. A total of 170 respondents were selected through convenience sampling. Data were collected via face-to-face interviews using a structured questionnaire, including sociodemographic details and Zarit Burden Scale. Statistical analysis was performed using SPSS, with ordinal logistic regression used to identify determinants of caregiver burden. Results: Present study showed that majority of the respondents (72.4%) experienced mild to moderate burden, less than two-fifths (15.3%) experienced moderate to severe burden, few of the respondents(9.4%) experienced little or no burden and only2.9%experienced severe burden. Marital status, habit of alcoholism, smoking or substance use, patient’s sex, duration of dialysis, availability of caregiving support and difficulty in meeting health expenses were identified as key determinants of caregiver burden. (p